2019
DOI: 10.3747/co.26.5531
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from a Cancer Knowledge Translation Grants Program: Results of an Evaluation

Abstract: Background   A novel way to build capacity in knowledge translation (KT) is through KT-focused grant competitions. Since 2009, the Knowledge Translation Research Network (KT-Net) has had a cancer-related KT grants program. We undertook an evaluation of the program to determine if KT-Net was achieving its aims of building capacity in cancer KT, advancing the science of KT, building partnerships, and leveraging funding.Methods   An adapted framework guided the evaluation. Nine funded studies from 4 competitions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The second insight is about the relational goals in strategies for KMb capacity development. Beyond offering opportunities for co-learning and developing trust among partners (Straus et al, 2011), relational strategies can be impactful in building the capacities for KMb by helping to produce more relevant research outputs and educating participants to engage in KMb activities (Gerrish, 2010;Dilkes et al, 2011;Boyko et al, 2012;Allen et al, 2013;Murnaghan et al, 2013;Restrepo et al, 2014;McCay et al, 2015;Mansilla et al, 2017;Mulvale et al, 2017;Hung et al, 2018;Dannevig et al, 2019;O'Brien et al, 2019). For instance, Edelstein (2016); Haynes et al (2020); Hope (2016); Cooper et al (2017) found that research partnerships with community partners build capacity for research use by giving more access to data, providing professional development opportunities, and creating more outputs for knowledge users, making KMb 'built-in' to research projects, and inducing more systemic changes.…”
Section: Discussionmentioning
confidence: 99%
“…The second insight is about the relational goals in strategies for KMb capacity development. Beyond offering opportunities for co-learning and developing trust among partners (Straus et al, 2011), relational strategies can be impactful in building the capacities for KMb by helping to produce more relevant research outputs and educating participants to engage in KMb activities (Gerrish, 2010;Dilkes et al, 2011;Boyko et al, 2012;Allen et al, 2013;Murnaghan et al, 2013;Restrepo et al, 2014;McCay et al, 2015;Mansilla et al, 2017;Mulvale et al, 2017;Hung et al, 2018;Dannevig et al, 2019;O'Brien et al, 2019). For instance, Edelstein (2016); Haynes et al (2020); Hope (2016); Cooper et al (2017) found that research partnerships with community partners build capacity for research use by giving more access to data, providing professional development opportunities, and creating more outputs for knowledge users, making KMb 'built-in' to research projects, and inducing more systemic changes.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Current Oncology, we report the results of an evaluation of KT-Net's grants program 10 . The evaluation concluded that the program achieved its aims of building capacity in cancer kt research, especially among researchers new to kt; making contributions to advancing the science of kt; building strategic partnerships; and leveraging funding.…”
Section: Impact Of the Knowledge Translationmentioning
confidence: 99%